Gastroprotective effect of the ethanolic extract and fractions obtained from syngonanthus bisulcatus Rul - Batista, Leônia Maria; de Almeida, Ana Beatriz Albino; Lima, Gedson Rodrigues de Morais; Falcão, Heloina de Sousa; Ferreira, Anderson Luiz; Magri, Luciana de Pietro; Coelho, Roberta Gomes [UNESP]; Calvo, Tamara Regina [UNESP]; Vilegas, Wagner [UNESP]; Brito, Alba Regina Monteiro Souza (My University, 2013)
Syngonanthus bisulcatus Rul., popularly known in Brazil as sempre-vivas chapadeira, is a plant of the family Eriocaulaceae, it is found in the states of Minas Gerais and Bahia. In this work, the ethanolic extract (EtOHE), flavonoid-rich (FRF), and flavonoid-deficient (FDF) fractions obtained from scapes of S. bisulcatus were investigated for gastroprotection in both rats and mice. The activity was evaluated in models for induced gastric ulcer (absolute ethanol, stress, non-steroidal anti-inflammatory drugs, and pylorus ligation). The participation of mucus and prostaglandin E2 were also investigated. Sb-EtOHE (50, 100, and 250 mg/kg, p.o.), Sb-FRF (100 mg/kg, p.o.), and Sb-FDF (100 mg/kg, p.o.) significantly reduced gastric injuries in all models. Sb-FRF altered gastric juice parameters after pylorus ligation. Sb-FRF and Sb-FDF (100 mg/kg each, p.o.) significantly increased the amount of adherent mucus in the gastric mucosa. Sb-FRF maintained the mucosal levels of prostaglandin after the administration of indomethacin. The results indicate that Sb-EtOHE, Sb-FRF and Sb-FDF have significant gastroprotective activity. The observed gastroprotective effects of S. bisulcatus probably involve the participation of both mucus and prostaglandins, integral parts of the gastrointestinal mucosa's cytoprotective mechanisms against aggressive factors. © 2013 Reproduction is free for scientific studies.
Keywords: Eriocaulaceae; Gastric ulcer; Gastroprotective activity; Medicinal plants; Syngonanthus bisulcatus; antiulcer agent; cimetidine; lansoprazole; plant extract; prostaglandin E2; Syngonanthus bisulcatus extract; unclassified drug; animal experiment; animal model; controlled study; dose response; drug dose comparison; drug effect; drug efficacy; drug mechanism; drug screening; male; mouse; nonhuman; phytochemistry; rat; stomach juice; stomach mucosa; stomach protection; stomach ulcer; Mus; Rattus; Syngonanthus